2005
DOI: 10.2143/ac.60.5.2004979
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial infarction as an uncommon clinical manifestation of intravascular large cell lymphoma

Abstract: Intravascular large cell lymphoma (IVL) is a very rare variant of non-Hodgkin's lymphoma presenting with puzzling clinical manifestations. There is a predilection for the central nervous system, but the tumour often affects also skin, lung, and kidneys while lymphadenopathy and hepatosplenomegaly are usually absent. Myocardial infarction due to IVL has not been reported so far. We here report on a 56-year-old patient who was admitted to our hospital with fever and clinical signs of erysipelas. He had a 6-month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Proof of this supposition, however, can only come from extensive evaluation of integrin expression in IVL cases from disparate organs. Beyond these major presentations, there are single case reports of IVL presenting primarily in almost every organ system; as interstitial lung disease [18], adrenal failure [19], pulmonary hypertension [20], nephrotic syndrome [21], myocardial infarction [22], and symmetric polyarthritis [23].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Proof of this supposition, however, can only come from extensive evaluation of integrin expression in IVL cases from disparate organs. Beyond these major presentations, there are single case reports of IVL presenting primarily in almost every organ system; as interstitial lung disease [18], adrenal failure [19], pulmonary hypertension [20], nephrotic syndrome [21], myocardial infarction [22], and symmetric polyarthritis [23].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…In relation to this possibility, Bauer et al [16] and Sumer et al [17] reported 2 exceptional IVLBCL cases in which fatal multiembolic strokes including myocardial infarction developed.…”
Section: Discussionmentioning
confidence: 99%
“…Otras formas de presentación poco frecuentes incluyen insufi ciencia suprarrenal, hipertensión pulmonar, síndrome nefrótico, infarto de miocardio y enfermedad pulmonar intesticial. La fi ebre en tanto se observa hasta en 45% de los casos, explicado por la producción de citocinas proinfl amatorias por parte de los linfocitos neoplásicos 1,[16][17][18][19][20][21][22] . Anemia (63%), LDH y b2-microglobulina elevada (82% y 86% respectivamente) son las alteraciones más comunmente observada al laboratorio, menos frecuentemente trombocitopenia y leucopenia (24 y 29%, respectivamente) 1,2,6 ; presentando el caso reportado anemia (29,9%) y leve trombocitopenia (106.300).…”
Section: Discussionunclassified